Impact of radiotherapy in head and neck regions on periodontal and oral hygiene conditions (Research, Society and Development, 2021)
Objective: Evaluate the influence of head and neck radiotherapy dose on periodontal tissue for to understanding of its adverse effects, and consequently to propose strategies to reduce its severity. Methodology: An observational, longitudinal and prospective study with intraoral clinical examinations performed before radiotherapy (T0) and immediately after the end of radiation therapy. The clinical data collected regarding oral and periodontal hygiene conditions were visible plaque index (VPI), gingival bleeding index (GBI), probing depth (PD), gingival recession area, clinical attachment level (CAL), degree of mobility and presence or absence of suppuration. In addition, data such as radiation dose, fractionation and duration of radiotherapy were reported. Results: Fourteen patients were evaluated, of which 11 had periodontitis after the radiotherapy, and 9 had poor oral hygiene conditions after the radiotherapy. Seven of the 11 subjects with periodontitis presented tumors in the oral cavity. There was a decrease in visible plaque index (VPI) and gingival bleeding index (GBI). The research was unable to establish a significant association between radiation therapy and oral hygiene condition and periodontitis. Conclusion: Poor oral hygiene conditions predominated in the sample, which can be associated with the presence of debilitating conditions. Direct radiation on the oral cavity may have an influence on the development of periodontitis. The development of gingivitis only and periodontitis was not influenced by dose, fraction or duration of radiotherapy in the study period.